Strategi Pengembangan Waralaba: Kasus Bisnis Waralaba 'Menantea' di Tebet - Anggita, Syafimah; Wafdannida, Wafdannida; Ariesty, Amelia (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Currently, drinks and food can be processed with various variations and creations that make people compete to make new breakthroughs in the culinary field. This is driven by technological developments, so the culinary business is growing and there is competition among culinary businessmen. Various culinary businesses are now opening up business opportunities through franchising as a business development strategy in order to reach more consumers. Development and marketing strategies are needed because they greatly influence the development of the culinary franchise business. This study aims to determine the development and marketing strategy of the ‘Menantea’ franchise business, which is currently on the rise amid the dense franchise business. The method used in this study is qualitative, with data collection using interviews, literature studies, and documentation. Based on the results of the analysis, the ‘Menantea’ franchise business has four capitals according to Pierre Bourdieu's conceptual theory, namely economic capital, social capital, cultural capital, and symbolic capital, in developing the ‘Menantea’ business in the midst of the franchise business arena.